COVID-19 antibody donation using immunoadsorption: Report of two cases. (October 2021) - Rothenburg, Jannik; Rink-Baron, Silke; Mueller, Lisa; Ostermann, Philipp Niklas; Fischer, Johannes; Stegbauer, Johannes; Moldenhauer, Anja
Abstract: For more than a year the whole world is suffering from the COVID-19 pandemic with no treatment option in sight. Administration of plasma from convalescent donors containing anti-SARS-CoV-2 antibodies, though promising according to case reports, failed to show a clear benefit in a greater number of trials. One reason could be varying and low antibody contents in a majority of plasma units hampering standardization and clinical efficacy. Besides, other plasma components unnecessarily transfused like coagulation factors might promote hypercoagulation seen in severe COVID-19 etiopathology. We therefore hypothesized that instead of collecting whole plasma units, convalescent donors could donate solely immunoglobulins by undergoing immunoadsorption, a mode of therapy regularly applied in autoimmune diseases. Here, we report the results of the first two antibody donations performed at the University Hospital Düsseldorf. In both cases, immunoadsorptions were very well tolerated with no side effects. Collected and neutralized eluates were concentrated using tangential flow filtration increasing the concentration of immunoglobulins 10fold as compared to peripheral blood and leading to probably eight times more neutralizing antibodies than in one plasma unit. Therefore, immunoadsorption can be used as a method of antibody donation. Whether these donated antibodies can be used as passive immunization in acutely infected patients remains to be elucidated.